STRATEGI MANAJEMEN KEPEMIMPINAN TERHADAP ETOS KERJA KARYAWAN DI BMT UGT SIDOGIRI TABANAN BALI - Ahmad Hamdi (Al-Idarah, 2021)
Leadership is an ability that comes from a person, that is, a leader must have a leadership management strategy because a leader is identical to the kholifah on earth, he must have a strong attitude to face all the risks that exist in the company because a leader really protects his men. From the above statement in this thesis the researcher intends to find out more about the leadership management that is owned by the company and then to correlate it with the implementation of leadership management and supporting and inhibiting factors in the application of leadership management. As for this study, the authors chose BMT UGT Capem Tabanan Bali as the research object. And in taking data sources are the leaders and employees of this study.